Gambaran Sistem Penyimpanan Obat Di Puskesmas “A” Kota Makassar - Megawati, Megawati; Sawitri , Windi (Jurnal Farmasi Sandi Karsa, 2023)
The drug storage system is a drug storage management activity carried out at Puskesmas "A" Makassar City. This study aims to determine the suitability of the drug storage system at Puskesmas "A" Makassar City based on the Regulation of the Minister of Health of the Republic of Indonesia No. 74 of 2016 concerning Pharmaceutical Service Standards at Puskesmas. The type of research used is observational research by observing research objects and variables and then the results are presented in a questionnaire/interview sheet in the form of a table. Based on the results of this research, it can be concluded that the drug storage system at Puskesmas "A" Makassar City has met the standards of Regulation of the Minister of Health of the Republic of Indonesia No. 74 of 2016 concerning Pharmaceutical Service Standards at Puskesmas, especially aspects of drug storage management. Although there are still several aspects that have not been fulfilled.